Ultimate collapse strength assessment of damaged steel plated grillages. (15th September 2015) - Underwood, James M.; Sobey, Adam J.; Blake, James I.R.; Shenoi, R. Ajit
Highlights: Damage strength assessment of steel plated grillages not previously presented. Ultimate collapse strength assessment of damaged steel grillages by FEA presented. Influence of damage aperture on collapse failure modes demonstrated. Concludes failure mode changes are critical to the ultimate collapse strength. Concludes structural idealisation must allow capture of failure mode changes. Abstract: Across many industries damage events leading to a breach in structural integrity continue to occur. An area where this can lead to particularly unsafe conditions is in the maritime environment, where it may be difficult to rescue crew and cargo. In order to improve structural safety through design for the survivability or to assess the residual strength of a damaged vessel in an emergency response or salvage scenario, it is critical to understand the influence of the damage. This paper, for the first time, investigates the use of FEA on ultimate collapse strength of damaged steel grillages and the influence of the damage aperture on the developing failure modes within the structure. The study finds that the presence of damage, in the form of a hole, can lead to the failure mode changing as damage aperture size is increased leading to significant changes to the ultimate collapse strength of the structure. It concludes that to assess the damaged strength of steel plated structures, it is critical that modelling methods are able to capture and account for such mode changes in order to accurately assess the true residual strength of the structure.